Французская интерпретация “русского нигилизма”: "Достоевский на Манхэттене" Андре Глюксмана - Dzyk, Roman (Verbum Praha, 2022)
The article deals with the interpretation of the phenomenon of nihilism, perceived through the prism of the Russian literature, given in the book Dostoevsky in Manhattan by A. Glucksmann. The similarities between the principles of the representative of the “new philosophy” and the concept of the “engaged literature by J.-P. Sartre are revealed. The article demonstrates that, in Glucksmann’s point of view, F. Dostoyevsky paradigmatically embodies the exposing message and prophetic features of the Russian literature.
French Іnterpretation of the „Russian Nihilism”: "Dostoevsky in Manhattan" by André Glucksmann
Keywords: F. Dostoevsky; Demons; nihilism; “new philosophy”; A. Glucksmann; intertext